Effects of beach erosion on abundance and distribution of toheroa (Paphies ventricosa) at Bluecliffs Beach, Southland, New Zealand - Michael P. Beentjes; Glen D. Carbines; Andrew P. Willsman (New Zealand Journal of Marine and Freshwater Research, 2006)
Data on abundance, distribution, and size structure of toheroa (Paphies ventricosa) on Bluecliffs Beach, Southland, New Zealand from 42 surveys (1966 to 2005) are presented. Toheroa abundance declined from over 2 million adults in the mid 1960s to c. 80000 by 1990 and since then has remained low but relatively stable. The decline mirrors that of other toheroa populations throughout New Zealand. Recent recruitment was highly variable but low compared with historical levels in the 1960s. Length frequency distributions are characteristically bimodal with a strong adult mode and a juvenile mode of variable strength, with relatively few toheroa of intermediate size. The distribution is related to mortality and growth characteristics of Bluecliffs Beach toheroa. Spatial distribution of adult toheroa has progressively changed over the last 40 years—historical distribution included the entire beach and toheroa were most dense just east of the Rowallan Burn. Since 1997, they have been aggregated into one large bed just west of the Rowallan Burn. Toheroa showed intertidal size zonation with small juveniles near high water and larger toheroa near mid to low water. Beach profile surveys were carried out in 1997, 2001, and 2005 to assess the dynamics of beach geomorphology and erosion. The surveys indicated a net loss of sand from the beach between 1997 and 2005, exposing underlying gravel and cobble substrates, and a general erosion of the vegetated dunes. Aerial photos from 1947 reveal that Bluecliffs Beach was homogeneous sand substrate—significant erosion and loss of sand began in the mid 1980s and only c. 54% of the beach surface is now fine/coarse sand. Our results indicate that distribution and abundance of toheroa on Bluecliffs Beach is related to the amount and distribution of sand on the beach. If the erosion continues with loss of sand habitat, the toheroa population may be at risk of collapsing.